Comparative Transcriptome Analysis Reveals Regulatory Factors Involved in Vibrio Parahaemolyticus Biofilm Formation - Wang, Qiuyu; Wang, Pengfei; Liu, Pingping; Ou, Jie (Frontiers in Cellular and Infection Microbiology, 2022)
Vibrio parahaemolyticus biofilm poses a serious threat to food safety and human health. However, there is limited knowledge of transcriptional regulatory mechanism during the biofilm formation of this organism. Hence, the RNA sequencing technique was employed to compare the differences in transcriptome profiles between planktonic and biofilm state of V. parahaemolyticus ATCC33847 in this study. Collections of mRNA from planktonic and biofilm cells cultured at 25 °C for 36 h were sequenced by studying their biological characteristics. The results showed that there were significant differences in the expression levels of 956 genes in biofilms compared with planktonic cells. These differences suggested that two-component regulatory system (TCS) and quorum sensing (QS) regulated V. parahaemolyticus biofilm formation by affecting important factors such as flagellar motility, EPS secretion, TRAP transport system and ABC transport system. The present work in transcriptomics serves as a basis for future studies examining the complex network systems that regulate bacterial biofilm formation.